Keberadaan Musik Gong Buleuh pada Masyarakat Kota Sungai Penuh Provinsi Jambi - Sepdwiko, Deria (UNIVERSITAS INDO GLOBAL MANDIRI)
This research was conducted to reveal the existence of Gong Buleuh Music in Sungai Penuh City Community, Jambi Province, this type of research is a qualitative research method of interpreting phenomena based on art issues in the Sungai Penuh community. The object of this research is the existence of Gong Buleuh music in the Sungai Penuh community of Jambi Province. Data collected through literature study, observation, interviews, and documentation. Data analysis was carried out based on ethnographic techniques. The findings of this study indicate that the existence of this Gong Buleuh music in the community plays an important role in the Kenduhai Sko ceremony. The uniqueness of an instrumental made of reeds in accordance with the ecological conditions of the Sungai Penuh city. Thus the existence of this Gong Buleuh music does not decline for the younger generation, of course, to explore its existence so that it is preserved by culture, especially Sungai Penuh City. Gong Buleuh music as a traditional art gives meaning to the life of the Kerinci community and its appearance has certain rules that must not be violated. If it is violated, there will be sanctions so that Gong Buleuh's music is a ritual in the Kenduri Sko ceremony. The Kenduri Sko ceremony, which is held once every ten years as a cleanser for heirlooms, is also a gathering place between layers of society. In this event without performing Gong Buleuh music, the ceremony is considered meaningless for the people of Sungai Penuh City. With the music of Gong Buleuh in the Kenduri Sko ceremony, the community can communicate with traditional and community leaders to officiate the opening of the Kenduri Sko.